2016
DOI: 10.1002/ajcp.12028
|View full text |Cite
|
Sign up to set email alerts
|

Thriving and Adapting: Resilience, Sense of Community, and Syndemics among Young Black Gay and Bisexual Men

Abstract: We examined resilience associated with the avoidance of psychosocial health conditions (i.e., syndemics) that increase vulnerability for HIV among young Black gay and bisexual men. We used analytic induction to compare a sample of 23 men who showed no evidence of syndemic conditions to a sample of 23 men who experienced syndemic conditions. The men who avoided syndemics reported supportive relationships with people who helped them to develop a strong sense of identity, provided them with opportunities to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 51 publications
2
40
1
Order By: Relevance
“…Using theoretically informed constructs, we defined resilience as the sum of 10 possible behavioural preferences or intentions that included: foreplay only or versatile sexual positions, being out about one’s sexual orientation identity, having a profile photo, seeking friendship, seeking a relationship, serosorting, not endorsing alcohol use, not endorsing drug use, sexual adventurism and safer sex. Consistent with prior research, 5,9,15,20,50,51 our content analysis of men’s profiles revealed that men endorsed a variety of resilience indicators (mean = 5.2; s.d. = 1.5; range = 0–9), despite networking in an online environment that may confer HIV risk.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Using theoretically informed constructs, we defined resilience as the sum of 10 possible behavioural preferences or intentions that included: foreplay only or versatile sexual positions, being out about one’s sexual orientation identity, having a profile photo, seeking friendship, seeking a relationship, serosorting, not endorsing alcohol use, not endorsing drug use, sexual adventurism and safer sex. Consistent with prior research, 5,9,15,20,50,51 our content analysis of men’s profiles revealed that men endorsed a variety of resilience indicators (mean = 5.2; s.d. = 1.5; range = 0–9), despite networking in an online environment that may confer HIV risk.…”
Section: Discussionsupporting
confidence: 88%
“…5,9,15,20,50,51 While a rich body of evidence generated since the beginning of the HIV epidemic highlights how psychosocial deficits and risk behaviours may contribute to the disproportionate vulnerability to HIV experienced by MSM (e.g. depression, substance use, childhood sexual abuse, sexual risk behaviour), 44,45,47,60,61 research is urgently needed to understand how HIV-risk resilience operates in different risk contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has indicated that strong social and family connectedness may help Black MSM avoid syndemics (Reed & Miller, 2016) and may be an important component to Treatment as Prevention, given the relationship between social support and viral load suppression (Simoni et al, 2006). Social support may also buffer the effects of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…For trans and non‐binary adults, developing bonding capital through intimate relationships and social networks may be an important part of resilience in the face of the dramatic reconfiguration of their social world that may occur after coming out. Connection to a supportive community is critical for the development and activation of resilience for transgender people (Singh, Hays, and Watson ), LGBTQ+ people in general, and LGBTQ+ people of color specifically (Reed and Miller ). Many scholars document the importance of positive and affirming social networks for transgender people in the United States, particularly social networks in person or online with other transgender people (Cavalcante ; Gray ; Pinto, Melendez, and Spector ; Shapiro ).…”
Section: Transgender Community and Resiliencementioning
confidence: 99%